2022
DOI: 10.1007/s12603-021-1713-4
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of SARS-CoV-2-Neutralising Antibodies of Residents of Long-Term Care Facilities

Abstract: Introduction Elderly residents of nursing homes (NHs) and long-term care units (LTCUs) have been shown to have a high risk of mortality and morbidity in cases of SARS-CoV-2 infection. The objective of this study was to examine the kinetics of neutralizing antibodies (NAbs) directed against the SARS-CoV-2 virus in residents of the NH and LTCU units of our University Hospital who were identified with positive serology after the first epidemic outbreak. Materials and Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
(29 reference statements)
0
1
1
Order By: Relevance
“…This is in contrast to a report showing that SARS-CoV-2 naï ve residents had lower antibody responses to BNT162b2 vaccination than naï ve staff [31]. A French study in a similar setting showed persistent humoral immunity against SARS-CoV-2 in residents, with a post-vaccination response lasting at least nine months in those who were previously infected, and lower in those who were seronegative before vaccination [32]. This is no different than in other age groups since waning of the vaccinal humoral immune response in the absence of re-stimulation is a normal immunological phenomenon and has been well established after vaccination against SARS-CoV-2 [33][34][35], leading to introduction of booster doses.…”
Section: Discussioncontrasting
confidence: 93%
“…This is in contrast to a report showing that SARS-CoV-2 naï ve residents had lower antibody responses to BNT162b2 vaccination than naï ve staff [31]. A French study in a similar setting showed persistent humoral immunity against SARS-CoV-2 in residents, with a post-vaccination response lasting at least nine months in those who were previously infected, and lower in those who were seronegative before vaccination [32]. This is no different than in other age groups since waning of the vaccinal humoral immune response in the absence of re-stimulation is a normal immunological phenomenon and has been well established after vaccination against SARS-CoV-2 [33][34][35], leading to introduction of booster doses.…”
Section: Discussioncontrasting
confidence: 93%
“…Although a reduced VE in the population aged above 60 was reported [ 24 ], the above-mentioned Hungarian study found the VE in individuals over 65 to be at least as good as in the younger population [ 22 ]. Since the ability to mount an adequate immune response following vaccination has been shown to be well preserved in older adults [ 26 , 27 , 28 ], increased VE in this population may be attributed to decreased exposure to the virus given that older categories of the population are the most inclined to closely follow the required epidemiological measures. Whatever the underlying reason(s), this is just as well since the highest proportion of the population in Serbia had received this vaccine, including in our study group.…”
Section: Discussionmentioning
confidence: 99%